α7-nicotinic acetylcholine receptor activation mitigates neuroinflammation associated with hypoxia-reoxygenation injury in zebrafish model - Mohammad Yusuf Hasan; Azim Haikal Md Roslan; Norazrina Azmi; Norlinah Mohamed Ibrahim; Alina Arulsamy; Lin, Vanessa Lin Lee; Rosfaiizah Siran; Mohd Kaisan Mahadi (Penerbit Universiti Kebangsaan Malaysia, 2025)
Ischemic stroke is a leading cause of death worldwide, where reduced blood flow to brain tissues can cause potential permanent neurological damage. Current treatments, such as intravenous thrombolysis with tissue plasminogen activator and mechanical thrombectomy, aim to restore cerebral blood flow within hours of stroke onset, often associated with ischemic reperfusion injury. Emerging strategies target the α7-nicotinic acetylcholine receptor (α7nAChR) to resolve neuroinflammation in various pathological conditions; however, the therapeutic effects of these strategies in ischemic reperfusion injury remain unknown. This study investigates the neuroprotective and anti-inflammatory effects of α7nAChR activation in zebrafish following ischemia-reperfusion injury. The hypoxia/reoxygenation model was established by perfusing pure nitrogen gas in a hypoxia chamber for 10 min, followed by a 1-h recovery/reoxygenation in the beaker. Gene expression markers for proinflammatory and anti-inflammatory factors were examined using qRT-PCR from the surviving brain tissues. Mitochondrial dehydrogenase activity was measured to investigate the level of brain damage. A six-minute open tank test assessed behaviour, precisely the turning angle, distance travelled, maximum acceleration, and meandering. Hypoxia/reoxygenation significantly increased the expression of proinflammatory markers, such as TNF-α and IL-6, whereas an α7nAChR agonist reduced the expression of these markers. However, there was no discernible improvement in locomotor activity or brain damage in the agonist group, implying that the neurological impairment was not fully reversed following PNU 282987 pre-treatments.